The Influence of Self Leadership on Organizational Citizenship Behavior with Self-Efficacy as a Mediation Variable on Teachers of SMK Negeri Jakarta Pusat - Munawaroh; Susan Febriantina; Aldinah Suro Lathifah (IJHCM (International Journal of Human Capital Management), 2021)
The purpose of this study was to determine the effect of self-leadership on Organizational Citizenship Behavior by self-efficacy as a mediation variable in, Central Jakarta State Vocatonal School Teacher. The research method used by researchers was a survey method with a descriptive approach, the population used was vocational school teachers. The model in this study uses the path analysis model. The analysis technique used in this study uses SEM (Structural Equation Modeling) which is operated with the SmartPLS version 3.0 program for testing hypothesis. In this study also tested the detection of the effect of intervening variables through the Sobel test. The analysis technique carried out in PLS includes three stages, namely the analysis of the outer model, analysis of the inner model, and testing of hypotheses. The results of the study are that self-leadership has a positive and significant effect on Organizational Citizenship Behavior, self-efficacy has a positive and significant effect on Organizational Citizenship Behavior, self-leadership has a positive and significant effect on self-efficacy, and self-leadership has a positive and significant effect on Organizational Citizenship Behavior with efficacy. self as a mediation between both.